Experience in surgical treatment of patients with traumatic spinal injuries associated with ankylosing spondylitis - I.V. Basankin; A.A. Giulzatyan; A.A. Afaunov; K.K. Takhmazyan; I.E. Gritsaev; S.M. Stepanenko; M.I. Tomina; V.K. Shapovalov (Хирургия позвоночника, 2024)
Objective. To analyze characteristics, diagnostic features and results of surgical treatment of patients with traumatic spinal injuries associated with ankylosing spondylitis. Material and Methods. A retrospective analysis of the results of surgical treatment of 32 patients (25 men and 7 women) operated on in 2019–2022 was performed. Results were followed-up during 12 months in all patients. Patient characteristics, diagnostic features, clinical outcomes, and the range of postoperative complications were reviewed. Results. The number of damaged levels in the cervical, thoracic and lumbar spine was 39. Low-energy injury (fall from a height and from a sitting position) was observed in 20 patients (62.5 %), and high-energy injury (fall from a height of more than 1 m and a road traffic accident) – in 12 patients (37.5 %). Type B3 fractures according to the AOSpine classification were present in 23 patients (71.8 %), and type C translational fractures – in 9 (28.2 %). CT of the spine and verification of the diagnosis were performed within 24 hours after the injury in 24 patients (75 %). The remaining 8 (25 %) patients underwent primary diagnosis later – in 19.8 ± 24.4 days (range 5–46 days). All patients underwent posterior fixation with or without decompression. The time of surgical intervention depended on the presence of neurological symptoms. Twenty one (65.6 %) patients with complicated injury underwent surgical intervention within 8 hours after admission to the hospital. In the remaining 11 (34.4 %) neurologically uncomplicated patients, operations were performed within 3.2 ± 1.4 days. In-hospital mortality was 6.25 % (n = 2), and 1-year mortality was 28 % (n = 9). There were no neurological symptoms before or after surgery in 11 patients (36.7 %). In the group of patients with initial neurological complications (n = 21), 3 (14.3 %) patients had complete regression of neurological symptoms (from AIS D to AIS E), 4 (19 %) - incomplete regression of symptoms (from AIS C to AIS D), and 14 (66.7 %) patients did not show significant positive dynamics. Pulmonary embolism (PE) and pneumonia were observed in 5 (15.6 %) and 6 (18.75 %) patients, respectively. In the postoperative period, the deep vein thrombosis of the lower extremities was most frequent (n = 9; 28.1%), and in 5 cases it was complicated by PE. Conclusion. The basis for diagnosing fractures in patients with ankylosing spondylitis is clinical data (increased pain after a fall and/or the appearance of neurological deficit) and radiological data (CT scan of the whole spine). Fractures in ankylosing spondylitis are characterized by absolute instability with a high risk of developing secondary neurological deficits in the case of conservative treatment or delayed surgical intervention. The essence of the surgery is the use of extended fixation with 8 screws in the cervical spine and more than 10 screws in the thoracic and lumbar spine. The most common complications of the early postoperative period include liquorrhea, surgical wound suppuration, pulmonary embolism, pneumonia, and loosening of transpedicular screws.